A unified modelling method for cyber-physical systems based on Modelica. (30th May 2019) - Chen, Chang; Cao, Han; Su, Shaohui; Chen, Huipeng; Gong, Youping; Chen, Guojin
Cyber-Physical Systems (CPS) are complex systems which consist of discrete asynchronous clock systems and continuous synchronous time systems that are different in structure and mathematics basis. This research aims to establish a unified modelling method for CPS based on the Modelica semantic. According to framework of the existing semantic, the clock semantics are proposed to describe the clock system. The decomposition method is proposed to separate the clock system into several sub-blocks that have different clock frequencies. The clock diffusing rules, consisting of single clock diffusing, clock consistent rule and clock super rule are presented to access the variables and expressions between each pair of sub-blocks. At last, the semantic integration between time and clock sub-systems is researched. The proposed method suggests that the CPS model could be built in a unified framework and the clock system and time system could be linked automatically.